Effects of organic and inorganic fertilizers on growth, yield and quality of lettuce (Lactuca Sativa L.) in rooftop garden (Bangladesh Journal of Botany, 2026)
A pot experiment was conducted in the rooftop garden to find the effects of organic and inorganic fertilizers in soil-based media on growth, yield and antioxidant properties of lettuce. Twelve different soil-based media prepared with different proportion of cowdung, vermicompost and biochar with four replications. Plant height, leaf number, shoot weight increased in the treatments of cowdung either used sole or together with vermicompost and biochar in soil compared to control and T1 (soil 100% + inorganic fertilizer) treatments. The antioxidant compounds of lettuce leaf such as vitamin C, phenolic and flavonoid content increased with the sole application of organic fertilizers and combined use of inorganic and organic fertilizers than control. But these antioxidants content decreased in the treatments treated with inorganic fertilizers. The antioxidants properties were consistent with DPPH activity of leaf extract as measured in IC50 value. Therefore, it is suggested that application of organic fertilizer in soil-based media improves the yield and quality of lettuce grown in the rooftop garden.Bangladesh J. Bot. 55(1): 223-227, 2026 (March)